The Influence of Adalimumab and Cyclosporine A on the Expression Profile of the Genes Related to TGFβ Signaling Pathways in Keratinocyte Cells Treated with Lipopolysaccharide A - Iwona Adwent; Beniamin Oskar Grabarek; Marta Kojs-Mrożkiewicz; Ryszard Brus; Rafał Staszkiewicz; Andrzej Plewka; Michał Stasiowski; Anita Lyssek-Boroń (Mediators of Inflammation)
Background. In the treatment of moderate to severe psoriasis, cyclosporine A (CsA) conventional therapy is used and biological, anti-cytokine treatment using, for example, anti-TNF drug—adalimumab. Aim. This study aimed at investigating the effect of CsA and adalimumab on the profile of mRNAs and protein expression associated with transforming growth factor β (TGFβ) pathways in human keratinocyte (HaCaT) culture previously exposed to lipopolysaccharide (LPS). Materials and Methods. HaCaT culture was exposed to 1 ng/ml LPS for 8 hours+8 μg/ml adalimumab for 2, 8, and 24 hours or 1 ng/ml LPS for 8 hours+100 ng/ml CsA for 2, 8, and 24 hours and compared to the control culture. Sulphorodamine B cytotoxicity assay was performed. The expression profile of mRNA related to TGFβ paths was indicated by microarray and RTqPCR analyses. The ELISA test was used to analyze changes on the proteome level. Statistical analysis consisted of ANOVA analysis and the post hoc Tukey test (p<0.05). Results. The cytotoxicity test showed that LPS, adalimumab, and cyclosporine in the concentration used in this experiment did not have any cytotoxicity effect on HaCaT cells. The largest fold changes (FC) in expression in (∣FC∣>4.00) was determined for TGFβ1-3, TGFβRI-III, SKIL, SMURF2, SMAD3, BMP2, BMP6, JAK2, UBE2D1, SKP2, EDN1, and PRKAR2B (p<0.05). In addition, on the protein level, the direct changes observed at mRNA were the same. Conclusion. Analysis of the microarray expression profile of genes associated with TGFβ signaling pathways has demonstrated the potential of cyclosporin A and adalimumab to induce changes in their transcriptional activity. The anti-TNF drug seems to affect TGFβ cascades to a greater extent than cyclosporin A. The obtained results suggest that the regularity of taking the drug is important for the efficacy of psoriasis therapy.